RISK FACTORS ASSOCIATED WITH BOVINE MASTITIS - Bomfim, Vitoria Vilas Boas da Silva; Balieiro, Amanda Costa; Costa, Ana Carolina Messias de Souza Ferreira da; Romeiro, Edenilze Teles; Franco, Eryvelton de Souza; Neves, Maria Luciana Menezes Wanderley; Marinho, Glenda Lídice de Oliveira Cortez; Farias, Márcia Paula Oliveira (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Identifying danger elements for mastitis is imperative for the improvement of particular techniques to manage and forestall the disease. Considering that these elements might also range between areas and dairy farms, the goal of this work was once to evaluation the fundamental threat elements related with bovine mastitis, each scientific and subclinical, in distinct countries, additionally overlaying epidemiological factors of the sickness such as etiology and prevalence. Factors related with bovine mastitis may additionally be associated to the animal, the environment, herd administration and milking equipment. Risk elements for mastitis related with the animal can also be the depth of the udder, the presence of hyperkeratosis on the teats and udder hygiene. Other elements related with a greater hazard of mastitis, such as a greater wide variety of births/lactations/age, greater lactation stage/days in lactation and greater proportion of Holsteins in the herd. Factors related with decrease possibilities of mastitis are: carrying out a milking line, that is, milking cows with mastitis after wholesome cows or separately, the usage of disposable gloves at some stage in milking, pre-milking teat disinfection, drying teats, post-milking teat disinfection and ordinary protection of milking equipment. Regular mastitis research proceed to be imperative for adapting and creating new equipment for controlling and stopping the disease.